Activities of fluoroquinolone, macrolide, and aminoglycoside drugs combined with inhibitors of glycosylation and fatty acid and peptide biosynthesis against Mycobacterium avium. - Barrow, W W (1993)
Smooth- and rough-colony variants of Mycobacterium avium serovar 4 were treated with three classes of drugs. The drugs were chosen for their potential inhibitory effects on the biosynthesis of the cell envelope-associated serovar-specific glycopeptidolipid antigens. Growth was monitored radiometrically with a BACTEC 460-TB instrument, and MICs were determined for each drug. Both variants were then treated with inhibitory drugs in combination with antimicrobial agents that have demonstrated effectiveness against M. avium. No growth inhibition was observed with 6-fluoro-6-deoxy-D-glucose or avidin. Inhibitors of glycosylation, i.e., 2-deoxy-D-glucose, bacitracin, and ethambutol, were inhibitory to smooth- and rough-colony variants, whereas drugs that inhibit peptide synthesis, i.e., N-carbamyl-L-isoleucine and m-fluoro-phenylalanine, were more inhibitory for the rough-colony variant. Cerulenin, which affects fatty acid synthesis, was inhibitory for both variants, but it appeared to be more effective at inhibiting the growth of the smooth-colony variant at equivalent concentrations. Generally, when inhibitors of glycosylation were used with sparfloxacin and amikacin, a synergistic effect was observed for only the smooth variant. When drugs that affect peptide synthesis were used in combination with amikacin, a synergistic effect was observed for the rough variant, and when cerulenin was used in combination with sparfloxacin or amikacin, a synergistic effect was observed for both variants. Lipid analysis revealed that although the rough variant lacks the serovar-specific glycopeptidolipid antigens, it does possess a group of phenylalanine-isoleucine-containing lipopeptides that may explain its different susceptibility patterns to m-fluoro-phenylalanine and N-carbamyl-L-isoleucine. The significance of these results is discussed with reference to various components in the cell envelope and their importance in cell wall permeability.